Fast residual stress mapping using energy-dispersive synchrotron X-ray diffraction on station 16.3 at the SRS. - Korsunsky, A; Collins, S; Owen, R; Daymond, MR; Achtioui, S; James, K (2002)
Synchrotron energy-dispersive X-ray diffraction experiments on station 16.3 at the SRS for residual strain mapping are reported. A white beam with an energy-discriminating detector allows measurements to be made through 3 mm Al, Ti, Fe and Cu alloys with acquisition times of approximately 30 s per 0.3 mm(3) sampling volume. The collected profiles were analysed using single-peak fitting and whole-pattern Pawley refinement, and produced strain accuracy better than 10(-4). This configuration is therefore highly efficient for fast strain mapping in thin components using a second-generation synchrotron source.